Clinical and Radiological Outcomes of Dura-Splitting versus Duraplasty Techniques in Pediatric Chiari I Malformation: A Systematic Review and Meta-Analysis - Tavallaii, Amin; Keykhosravi, Ehsan; Ghorbanpour, Ahmad; Shahriari, Ali; Rezaee, Hamid (Asian Journal of Neurosurgery, 2023)
Type I Chiari malformation is a developmental anomaly with various proposed surgical techniques for its management. The dura-splitting technique is a less invasive approach and involves the resection of the outer layer of the dura while sparing the internal layer. While this less-known approach may minimize the complication rates, there are concerns about its efficacy and outcome. Therefore, we have performed a systematic review and meta-analysis of available data on clinical and radiological outcomes of this technique in the pediatric population and compared them to the foramen magnum decompression and duraplasty technique.We have followed the Meta-analysis Of Observational Studies in Epidemiology guidelines in this review. Based on our predefined search strategy, we performed a systematic database search. Subsequently, the article screening process was done based on defined inclusion/exclusion criteria. Following the quality assessment of included studies, two authors performed data extraction. Finally, the extracted data were summarized and presented in form of tables. Forest plots were used to demonstrate the results of the meta-analysis.A review of 8 included studies consisting of 615 patients revealed the significant advantage of the dura-splitting technique in terms of shorter operation duration and hospital stay. The recurrence rate and clinical and radiological outcomes were almost similar between the two surgical techniques. Complication rates were significantly lower in the dura-splitting technique.Dura-splitting can be an effective and safe approach for the management of pediatric Chiari I malformation. However, these results are mostly extracted from observational studies and future randomized controlled trials are recommended.
Keywords: Chiari malformation type I; dura-splitting; duraplasty; outcome; pediatric